Temel Muhasebe Varsayımları ve Muhasebe Politikalarına Yön Veren Kavramlar - (:unkn) unknown (My University, 2002)
0

According to Turkish Accounting Standard- 1: Disclosure of Accounting Policies, fundamental assumptions of accounting as follows: 1- Continuing- concern concert 2- Consistency 3- Matching principle Also, the following considerations are important to select of accounting policies: 1- Conservatism 2- Substance over form 3- Materiality The aim of this study is to state above concepts as practical.